Combining Petrology and Seismology to Unravel the Plumbing System of a Typical Arc Volcano: An Example From Marapi, West Sumatra, Indonesia. (22nd April 2021) - Nurfiani, D.; Wang, X.; Gunawan, H.; Triastuty, H.; Hidayat, D.; Wei, S. J.; Taisne, B.; Bouvet de Maisonneuve, C.
Abstract: Marapi in Sumatra is characterized by frequent short‐lived explosions and small eruptions (Volcanic Explosivity Index 1–2) and in the past 250 years, the volcano has erupted >60 times. Recent volcanic bombs and the presence of broadband seismic stations lead us to reconstruct the plumbing system of the volcano through an interdisciplinary study. A petrologic study of the summit bombs uses pyroxene, plagioclase and glass compositions to obtain pressures and temperatures of magma storage as well as identify pre‐eruptive processes. Two‐pyroxene geothermobarometry provides pre‐eruptive crystallization pressure estimates of 4–7 kbar (∼15–26 km). Compositional and textural analyses of plagioclase and pyroxene crystals indicate that mafic magma recharge was followed by mixing with the resident magma and renewed crystallization prior to eruption. In order to further image the magma reservoir, we performed a joint inversion of teleseismic receiver functions and surface waves (H/V ratio). The inversion reveals a low velocity zone (LVZ) at depths of 15–21 km that has 7 ± 3% shear velocity reduction, corresponding to an estimated melt fraction of 5 ± 2%. The depth of this LVZ overlaps with the depth of magma storage estimated from petrology, constraining it with high confidence. Such a combined interdisciplinary study provides valuable information for evaluating future periods of unrest, laying out a framework for the interpretation of incoming monitoring data and signals to look out for in order to improve eruption forecasts. Plain Language Summary: Magma plumbing systems (MPS) are the network of interconnected magma ponding regions beneath active volcanoes. The activities within the MPS involve processes such as crystallization of magma, injections of a new magma batch from a deeper source, mixing with the pre‐existing magma, and magma transport to shallower depths or to the surface leading to an eruption. Understanding the processes in the MPS will provide information for interpretation of past and current eruption behavior for improved hazard assessments and eruption forecast. We study the MPS of Marapi (Sumatra) with the analysis of erupted rock samples and seismic waves propagating through the MPS. We find that the magma storage of Marapi is located at ∼15–26 km beneath the volcano where magmas are stored in a state containing mostly solid crystals with low average melt (liquid phase) fractions. Crystals in the erupted rock samples record the injection of a new magma, its mixing with the pre‐existing (resident) magma and renewed crystallization before eruption. This study will provide a framework for the interpretation of incoming monitoring data and signals to look out for in order to improve eruption forecasts. Key Points: Combined petrologic and seismic studies constrain the magma plumbing system of Marapi Marapi magmas are stored in a highly crystalline state with low average melt fractions Plagioclase crystals record magma recharge, hybridization with the resident magma, and renewed crystallization before eruption